PERGESERAN PEMBAGIAN WARIS ADAT DALAM SUKU BATAK ANGKOLA (STUDI DI KECAMATAN PADANGBOLAK KABUPATEN PADANGLAWAS UTARA) - RAMADHAN PUTERA BAKTI (PREMISE LAW JURNAL, 2017)
One of the characteristics of adat law in Inheritance Law is dynamic which means that it can change any time, along with community development; it can also be different from one place to another according to each community development. Batak Angkola tribe is one of the Batak ethnic groups that have long dwelled in Padanglawas Utara Regency. The result of the research showed that there was the shift in the Angkola adat (customary) inheritance law at two villages: Sosopan village and Purbasinomba village, Padangbolak Subdistrict, Padanglawas Utara Regency. It is caused by religious, educational, and economic factors. These three factors reflect positive mindset to achieve justice in distributing inheritance of the adat community in Padangbolak Subdistrict, Padanglawas Utara Regency. The people at Sosopan village and Purbasinomba village, who are Moslems, should maintain the values of distributing inheritance according to the Islamic law so that justice will be achieved. Keywords: Shift, Inheritance Law, Angkola Tribe